Utilization of Electrospun Polystyrene Membranes as a Preliminary Step for Rapid Diagnosis. Issue 7 (4th May 2016) - Isık, Tuğba; Horzum, Nesrin; Yıldız, Ü. Hakan; Liedberg, Bo; Demir, Mustafa M.
Abstract : This study develops an easy‐to‐use test platform toward the rapid diagnosis of many life threating diseases by using a commodity plastic (polystyrene). Deoxyribonucleic acid is isolated from bovine serum albumin using fibrous polystyrene membranes, which are extremely cheap and can be readily electrospun from solution under ambient conditions. Surface modification of the constituent electrospun filaments with Au nanoparticles improves the performance of the membrane. Abstract : Recent advances in clinical practice drive deoxyribonucleic acid (DNA) as an important class of biomarker. Monitoring the change in their concentration suggests the initiation and/or progression of various disorders. However, low quantity of DNA biomarkers in body fluids requires a delicate isolation methodology that provides efficient separation and easy handling. This study describes a newer‐generation separation technology relying on electrospun fibers of sub‐micrometer diameter of a commodity polymer for DNA biomarkers in simulative serum. Fibrous polystyrene membranes are prepared by electrospinning and they are subjected to post‐modification with Au. The composite membranes may provide a convenient environment for the removal of bovine serum albumin (BSA) from BSA and DNA mixtures. The eluent can be used as an efficient tool for detection of DNA biomarkers associated with diagnosis of numerous life‐threatening diseases.